Obszary działań nauczycieli w zakresie pomocy dzieciom z rodzin alkoholowych - Grabowiec, Anna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2018)
Instytucją mającą szerokie możliwości niesienia pomocy dzieciom z rodzin alkoholowych jest szkoła. Nauczyciele ze względu na częsty i regularny kontakt z dziećmi są w wyjątkowej sytuacji sprzyjającej pomocy i skutecznej interwencji. W artykule po krótkim opisie specyfiki funkcjonowania rodzin alkoholowych przedstawiono możliwości i obszary organizowania pomocy i wsparcia dla dzieci z rodzin alkoholowych w warunkach pracy szkoły.

The school is an institution which has a wide array of possibilities to help children from alcoholic families. Teachers, due to their frequent and regular contact with the children, are in a position to intervene successfully in the child’s situation. The article begins with a brief description of a the specificity of functioning of alcoholic families. Then, it presents the possible areas of help and specific ways in which schools can provide support to children from alcoholic families.
The Areas of Teacher Action in Helping Children from Alcoholic Families
Keywords: rodzina alkoholowa; dziecko; nauczyciel; pomoc; alcoholic families; child; teacher; support